Microcin determinants are associated with B2 phylogroup of human fecal Escherichia coli isolates - Micenková, Lenka; Bosák, Juraj; Štaudová, Barbora; Kohoutová, Darina; Čejková, Darina; Woznicová, Vladana; Vrba, Martin; Ševčíková, Alena; Bureš, Jan; Šmajs, David (MicrobiologyOpen, 2016)
Escherichia coli strains are classified into four main phylogenetic groups (A, B1, B2, and D) and strains of these phylogroups differ in a number of characteristics. This study tested whether human fecal E. coli isolates belonging to different phylogroups differ in prevalence of bacteriocinogenic isolates and prevalence of individual bacteriocinogenic determinants. A set of 1283 fecal E. coli isolates from patients with different diseases was tested for the presence of DNA regions allowing classification into E. coli phylogroups and for the ability to produce bacteriocins (23 colicins and 7 microcins). Of the isolates tested, the most common was phylogroup B2 (38.3%) followed by phylogroups A (28.3%), D (26.3%) and B1 (7.2%). Altogether, 695 bacteriocin producers were identified representing 54.2% of all tested isolates. The highest prevalence of bacteriocin producers was found in group B2 (60.3%) and the lowest in group B1 (44.6%). Determinants encoding colicins E1, Ia, and microcin mV were most common in phylogroup A, determinants encoding microcins mM and mH47 were most common in phylogroup B2, and determinant encoding mB17 was most common in phylogroup D. The highest prevalence of bacteriocinogeny was found in phylogroup B2, suggesting that bacteriocinogeny and especially the synthesis of microcins was associated with virulent and resident E. coli strains.
Keywords: gastrointestinální trakt; Phylogeny; Feces; E. coli; Bacteriocins; bakteriociny; Bacteriocin; Gastrointestinal Tract; koliciny; lidé; Escherichia coli; Colicins; colicin; feces; microcin; Humans; fylogeneze; phylogroup.